Magnetic core–shell CuFe2O4@C3N4 hybrids for visible light photocatalysis of Orange II - Yao, Y.; Lu, F.; Zhu, Y.; Wei, F.; Liu, X.; Lian, C.; Wang, Shaobin (Elsevier, 2015)
Novel CuFe2O4@C3N4 core–shell photocatalysts were fabricated through a self-assembly method and characterized by X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, transmission electron microscopy and Uv–vis diffuse reflection spectroscopy. The photocatalytic performances of the CuFe2O4@C3N4 catalysts were evaluated in photo Fenton-like discoloration of Orange II dye using H2O2 as an oxidant under visible-light irradiation (λ > 420 nm). It was found the CuFe2O4@C3N4 hybrid (mass ratio of CuFe2O4/g-C3N4 at 2:1) exhibits a superior activity as compared with single component of CuFe2O4 or g-C3N4 and the mixture of g-C3N4 and CuFe2O4, due to the elevation of the separation efficiency of photoinduced electron–hole pairs, resulted from the heterojunction between the interfaces of g-C3N4 and CuFe2O4. The quenching tests of different scavengers displayed that View the MathML sourceO2•−, radical dotOH and h+ are responsible for the Orange II decolorization. In addition, the effects of initial concentration of the dye contaminant (0.014–0.140 mM), different anions (Cl−, View the MathML sourceSO42−, View the MathML sourceNO3−, CH3COO− and View the MathML sourceHCO3−) and temperature (15–65 °C) in photoreaction were also investigated. The CuFe2O4@C3N4 sample exhibited stable performance without obvious loss of catalytic activity after five successive runs, showing a promising application for the photo-oxidative degradation of environmental contaminants.